Molecular interactions of organic molecules at the air/water interface investigated by sum frequency generation vibrational spectroscopy. Issue 6 (25th January 2017) - Wang, Wenting; Ye, Shuji
Abstract : Second-order Fermi resonanance interaction provides an effective vibrational optical ruler for characterizing the molecular interactions at interfaces. Abstract : The molecular structure and dynamics of organic molecules at the aqueous interface have attracted a number of investigations owing to their importance and specific nature. However, there are relatively few studies on the direct characterization of the molecular interactions at the air/water interface because they are extremely difficult to measure in experiments. In this study, we use dibutyl ester molecules (R1 CO2 R2 O2 CR1 ) as a model of organic molecules, and investigate their molecular structure and interactions using sum frequency generation vibrational spectroscopy. We demonstrate that the molecular interactions can be estimated by measuring the intensity ratio of the symmetric stretching ( ν 1 ) and Fermi resonant bands (2 ν 2 ) of methyl groups. Here, dibutyl ester molecules are widely used as plasticizers in polymers to improve the properties of the plastics and polymers. It is found that the orientation angles of the tailed methyl groups at the air/water interface decrease from 34° to 19° when the chain length of R2 increases from 0 to 8. The total intermolecular interactions of the dibutyl ester molecules decrease as the chain length of R2 increases because the van der Waals interactions between the hydrocarbon chains increase, while the hydrogen bond interactions between the carbonyl group and water molecules decrease. Our study demonstrates the stability of ester-based plasticizers in polymers can be well predicted from the intensity ratio of the ν 1 and 2 ν 2 bands of methyl group. Such an intensity ratio can be thus used as an effective vibrational optical ruler for characterizing molecular interactions between plasticizers and polymers.